Efficient sorting in a dynamic adverse-selection model - Igal Hendel; Alessandro Lizzeri; Marciano Siniscalchi (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2004)
We discuss a class of markets for durable goods where efficiency (or approximate efficiency) is obtained despite the presence of information asymmetries. In the model, the number of times a good has changed hands (the vintage of the good) is an accurate signal of its quality, each consumer self-selects into obtaining the vintage that the social planner would have assigned to her, and consumers' equilibrium trading behavior in secondary markets is not subject to adverse selection. We show that producers have the incentive to choose contracts that lead to the efficient allocation, and to supply the efficient output. We also provide a contrast between leasing contracts, resale contracts, and different kinds of rental contracts. Resale contracts do not lead to the efficient allocation. A specific kind of rental contract provides the appropriate incentives to consumers.
Keywords: 330